COMBINATION TREATMENT WITH OXALIPLATIN AND MANGIFERIN CAUSES INCREASED APOPTOSIS AND DOWNREGULATION OF NFÎšB IN CANCER CELL LINES - van de Venter, Maryna; du Plessis-Stoman, Debbie; du Preez, Jan GH (African Journal of Traditional, Complementary and Alternative Medicines, 2010)
Mangiferin-mediated down-regulation of NFÎºB showed potential for chemotherapeutic agent-mediated cell death, suggesting a role in combination therapy for cancer. In this study the combined mechanism of the anticancer action of oxaliplatin and mangiferin was investigated. MTT dose response curves, trypan blue staining, caspase 3 assays as well as DNA cell cycle analyses were performed on HeLa, HT29 and MCF7 cancer cell lines, with and without the addition of 10 Âµg/ml mangiferin. Mitochondrial membrane potential, DNA fragmentation, resistance induction studies and NFÎºB assays were performed on HT29 cells only. Addition of 10 Âµg/ml mangiferin reduced oxaliplatin IC50 values in HT29 (3.4 fold) and HeLa (1.7 fold) cells in the MTT assay while reducing trypan blue staining. This was accompanied by increased caspase 3 activation and DNA fragmentation and a delay in the S-phase of the cell cycle. Mitochondrial membrane permeabilization was not enhanced in the combination treatment. Mangiferin was shown to cause a reduction of NF-ÎºB activation in HT29 cells rendered resistant to oxaliplatin. The present study indicates that mangiferin in combination with oxaliplatin favours apoptotic cell death and thereby improves the efficacy of oxaliplatin in vitro. In addition, combination therapy with mangiferin may also counteract the development of resistance in cancer cell lines.